Problemy pedagogiki i jej badań w ponowoczesności - Śliwerski, Bogusław (Wydawnictwo Naukowe UAM, 2012)
The author analyses the issue of methodology of pedagogical research in the postmodern society from the perspective of other social and human sciences. This problem is associated within both concepts and contributes to divisions between various theoretical perspectives that lead to different paradigms in diagnostic research. Pedagogy is inevitably connected to values. However, this fact does not exclude it from sciences. Similarly to researchers in psychology and sociology, those conducting pedagogical research have to construct opinions and interpretations and further educational aims and requirements that must be secured to achieve them.
Pedagogy and Pedagogical Research in Postmodernity
Keywords: pedagogy; sociology; psychology; research methodology; theories; didactics; values; education; socialization